Calibration handbook of measuring instruments - Brunelli, Alessandro (Industrial instrumentation technologist) (International Society of Automation, 2017)
Calibration Handbook of Measuring Instruments is mainly written for operators involved in verifying and calibrating measuring instruments used in Quality Management Systems ISO 9001, Environment Applications ISO 14001, Automotive Industry ISO 16949, and Aviation Industry EN 9100. It is a handy reference and consultation handbook that covers useful topics on assuring and managing industrial process measurement, such as: • The general concepts for managing measurement equipment according to the ISO 10012 concerning the management system of instruments and measurements • An instrument's suitability to perform accurate measurements and control the drift to maintain the quality of the measurement process • The criteria and procedures for accepting, managing, and verifying the calibration of the main industrial measuring instruments • The provisions of law and regulations for production, European marking CE of metrological instruments used in commercial transaction and for their periodic verification Report templates that are useful for recording both the recorded instrument data and the experimental calibration data and evaluating the conformity of the instrument, are available on a CD for practical use. The CD also contains various spreadsheets in Excel, Reports Calibration, which automatically calculate errors and the relative measurement uncertainty for determining a calibrated instrument's compliance.